Synthesis and characterization of iron (III) complexes of l-leucine and l-methionine - Musa, Shuaibu; J F, Iyun; Musa Abubakar, Shuaibu (International Journal of Advanced Chemistry, 2019)
The resulted complexes produced between Fe (III) and biological molecules like amino acids play an important role in human life. Fe (III) complexes are synthesized with l-Leucine and l-Methionine. The complexes were characterized by elemental analysis (AAS), molar conductance, melting point, infrared and uv-visible spectrophotometry analyses. The elemental analyses were used to determine the chelation ratio, 1:3(metal: ligands). The molar conductivity of the complexes show that the complexes are not electrolytic in nature. Moreover, the melting point of the tris (l-Leucine) iron (III) and tris (l-Methionine) iron (III) are 2390C and 210oC respectively.Â Â